The Impact of a Qur’an-, Hadith-, and Historical Exemplar–Based Religious Literacy Intervention on Students’ Wasatiyyah Attitudes: a Pre-Experimental Study - R. Cecep Romli (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2025)
Religious illiteracy constitutes an epistemic problem that contributes to the reproduction of intolerant attitudes and discriminatory practices. Drawing loosely on the notion of Critical Religious Literacy (CRL), this study examines the impact of a religious literacy intervention on students’ wasatiyyah (moderate) attitudes. The study employs a pre-experimental design with a post-test administered to two intact groups of students, and the data are analyzed using Mann–Whitney U and Chi-square tests. The intervention draws on primary Islamic textual sources (the Qur’an and Hadith) and historical exemplars from the Prophet Muhammad and his Companions, framing religious moderation as an internal ethical commitment rooted within the Islamic tradition rather than as an externally imposed concept. The findings indicate that the intervention shifted students’ cognitive understanding of wasatiyyah and strengthened moderate attitudes across several issues, including support for Muslims’ obligation to protect all houses of worship and willingness to live as neighbors with Jews and Christians. However, the intervention did not produce behavioral change regarding students’ willingness to provide food to Jewish neighbors. Overall, the study suggests that religious literacy interventions grounded in Islamic textual and historical sources can effectively reinforce moderate religious attitudes, particularly at the cognitive and attitudinal levels, while behavioral change may require more sustained or intensive engagement. Ketidaktahuan tentang agama (religious illiteracy) merupakan persoalan epistemik yang berkontribusi terhadap reproduksi sikap intoleran dan praktik diskriminatif. Berangkat secara longgar dari gagasan Critical Religious Literacy (CRL), penelitian ini mengukur pengaruh intervensi literasi agama terhadap sikap wasathiyah (moderasi) siswa. Penelitian ini menggunakan desain pra-eksperimental dengan post-test pada dua kelompok siswa yang utuh (intact groups), dan data dianalisis menggunakan uji Mann–Whitney U dan Chi-kuadrat. Intervensi pembelajaran ini bertumpu pada sumber-sumber tekstual utama Islam (Al-Qur’an dan Hadis) serta keteladanan historis Nabi Muhammad dan para sahabatnya, dengan menempatkan moderasi beragama sebagai komitmen etis yang berakar dari tradisi Islam itu sendiri, bukan sebagai konsep yang berasal dari luar. Temuan penelitian ini menunjukkan bahwa intervensi ini berhasil menggeser pemahaman kognitif siswa tentang konsep wasathiyah dan memperkuat sikap moderat pada sejumlah isu, termasuk dukungan terhadap kewajiban umat Islam untuk melindungi seluruh rumah ibadah serta kesediaan hidup berdampingan sebagai tetangga dengan pemeluk agama Yahudi dan Kristen. Namun, intervensi ini tidak mendorong perubahan perilaku terkait kesediaan siswa untuk memberi makanan kepada tetangga yang beragama Yahudi. Secara keseluruhan, penelitian ini menunjukkan bahwa intervensi literasi agama yang berakar pada sumber tekstual dan historis Islam efektif dalam memperkuat sikap moderasi beragama, terutama pada ranah kognitif dan afektif, sementara perubahan pada ranah perilaku tampaknya memerlukan keterlibatan yang lebih berkelanjutan dan intensif.